Ethics of the Notary Profession and Challenges in the Digital Era - Rusdianto Sesung; Citra Mayasari (Budapest International Research and Critics University, 2022)
Notaries in carrying out their positions, notaries must comply with the Notary Code of Ethics. However, the rapid development of digital technology has led to legal changes, which have an impact on problems in the implementation of notary professional ethics. It is possible that Notaries will be trapped in new phenomena that can ensnare them into legal problems in the future. This research raises the issue of the form of implementing notary professional ethics and its challenges in the digital era. This research is a normative juridical research using a statutory, conceptual, and case approach. Legal materials were collected through literature study and analyzed using qualitative analysis. The results of the study conclude that the challenge for notary professions in the digital era, in implementing Notary ethics, is that a Notary must have skills (skills), knowledge (insight or knowledge), and attitude (attitude or behavior) to understand digital technology. Because, if the Notary does not understand the characteristics and intricacies of digital technology, it will slip into a deviation from Notary ethics. Notaries will find it difficult to sort out which ones are prohibited and allowed to promote on social media or on digital media. Notaries must master digital technology as a provision for the implementation of notary professional ethics in the digital era.